Synthesis and Characterisation of Mixed Copper(II) Complexes with 2,2´ -Bipyridine & 1, 10-Phenanthroline - Kumar Kathal, Mahesh; Gautam, R.K. (Asian Journal of Chemistry, 2010)
Mixed chelate complexes of composition [Cu(L)2](VO3)2nH2O, where L ═ bipy or phen (bipy ═ 2,2´-bipyridine and phen ═ 1,10-phenanthroline), n ═ 1 or 2 have been prepared and characterised through elemental analysis, molar conductance, magnetic susceptibility, electronic and infrared spectral data. The lattice constant and unit cell calculated with the help of powder diffraction pattern of complexes.